Miniature Pulpotomy of Symptomatic Mature Permanent Teeth: A Report of Two Cases - Asgary, Saeed; Nourzadeh, Mahdieh; Eghbal, Mohammad Jafar (Iranian Endodontic Journal, 2016)
Human dental pulp inflammation can progress to periapical lesion formation and conventional root canal treatment (RCT) has been the traditional method for disease management. This observational study presents two cases of vital pulp therapy in mature molars diagnosed with irreversible pulpitis and associated with apical periodontitis. In these two clinical cases, the involved teeth had deep carious lesions with a history of spontaneous/lingering pain and radiographic examinations revealed the presence of apical radiolucencies. A conservative miniature pulpotomy (MP) using calcium-enriched mixture (CEM) was performed and the teeth were permanently restored with amalgam. Clinical evaluations indicated resolution of pain 24 hours after treatment; the teeth showed normal vitality, remained asymptomatic and maintained normal function after recall examinations. Furthermore, the 18-month radiographic evaluation showed healing of the apical lesions. Vital pulp therapy using the MP technique with CEM appeared successful in avoiding RCT intervention. These two reports of case outcome suggest that simple MP using a CEM bioregenerative technique may provide a favorable outcome for permanent teeth diagnosed with irreversible pulpitis and associated with apical periodontitis. Keywords: Calcium-Enriched Mixture, CEM cement, Endodontic, Miniature pulpotomy, Irreversible pulpitis